The correlation between the level of 25-hydroxyvitamin D [25(OH)D] and residency of multiple sclerosis patients in Montenegro – higher levels only in men in the north of the country - Vujisic, Slavica M; Vodopic, Sanja; Idrizovic, Zilha; Radulovic, Ljiljana (Vojnosanitetski pregled, 2020)
Background/Aim. Multiple Sclerosis (MS) is a chronic neurological disease associated with low serum levels of 25-hydroxyvitamin D [25(OH)D]. The aim of this study was to determine the association between serum levels of 25(OH)D and the latitude as well as clinical MS severity and progression expressed by expanded disability status scale (EDSS) and multiple sclerosis severity score (MSSS). Methods. A total of 196 patients, from North and South of Montenegro, aged 18 to 65 years, with confirmed diagnosis of MS were recruited for the study. Serum samples were collected for 25(OH)D measurement. Control group consisted of 196 health controls, randomly selected from medical staff employed in health centers from three cities in North and Clinical Centre of Montenegro from the South. Results. The serum levels of 25(OH)D were significantly lower in MS patients compared to controls (p
Keywords: multiple sclerosis; vitamin d; geography, medical; severity of illness index; disease progression; sex factors; montenegro